Boarding School System in Strengthening The Religious and Moderate Character of Students at SMA Plus Al Fatimah Bojonegoro - Burhanuddin, Hamam; Hikmiah, Siti Nafisatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Boarding school is an educational institution where students not only study but also live and live together in the institution. The religious and moderate character students is an obedient attitude-behavior in carrying out religious teachings, tolerant the implementation worship other religions, and living in harmony with other religions. Integrity is the moderate nature of Islam that persists in a person so that these traits become a distinctive personality. This study uses a qualitative approach to the type of phenomenological research. Data collection was carried out using participatory observation techniques, interviews, and documentation. The results of this study contribute to the theory of the boarding school system in the formation of moderate and religious characters which consist of: (1) The concept of the boarding school system is carried through several steps, namely: (a) Establishment goals (b) Knowing the conditions and potential (c) Identifying supporting factors and obstacle, (d) Establishment the program. (2) Implementation of the boarding school system is carried out through (a) Approach (b) Exemplary (c) Awareness, (d) mentoring. (3) The role of the boarding school system includes: (a) The social role increasing independence, discipline, and awareness of students. (b) The role of religion supports noble values ​​that call for the principle of goodness.